Synthesis of Ethyl Arylpropiolates through Palladium-Catalyzed Cross-Coupling Reactions of Aryl Iodides with In Situ Generated Lithium Tetrakis(ethoxycarbonylethynyl)indates - Park, Youngchul; Kang, Dongjin; Jeon, Woo Hyung; Ryu, Taekyu; Lee, Phil Ho (Synthesis, 2014)
An efficient synthetic method to access ethyl arylpropiolates has been developed; it involves a palladium-catalyzed cross-coupling reaction between a wide range of aryl iodides and lithium tetrakis(ethoxycarbonylethynyl)indates (0.35 equiv) generated in situ from indium trichloride and alkynides obtained from ethyl propiolate and n-butyllithium.
Keywords: cross-coupling; palladium; indium; lithium tetrakis(ethoxycarbonylethynyl)indate; propiolates; catalysis